2014
DOI: 10.2190/tw.44.2.d
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives on the Technical Communication Internship: Professionalism in the Workplace

Abstract: This article argues for developing linked courses in technical communication where the instructor facilitates a service-learning curriculum and then serves as faculty advisor within subsequent internships. In these linked courses, students write technical documents before moving into internships where they write similar documents. Specifically, the article examines the results from one such class and offers both theoretical and practical advice for collaborating with nonprofit and creating internships that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Qualitative studies that have been reported in the literature recently provide descriptions of students in a particular context of a linked course (Bourelle, 2014). The qualitative lens allows me to provide "richer descriptions of the participants and their contexts than might be seen in a quantitative study" (Hughes & Hayhoe, 2008, p. 80), but as a result, the sample sizes of these groups are smaller.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative studies that have been reported in the literature recently provide descriptions of students in a particular context of a linked course (Bourelle, 2014). The qualitative lens allows me to provide "richer descriptions of the participants and their contexts than might be seen in a quantitative study" (Hughes & Hayhoe, 2008, p. 80), but as a result, the sample sizes of these groups are smaller.…”
Section: Methodsmentioning
confidence: 99%
“…As the tasks and activities in the workplace have other goals other than student learning, it is unclear how industry mentors make adjustments to help scaffold their interns into these experiences although they appear to support students through "contingent" scaffolding (Wilson & Devereux, 2014, p. A94) that happens at the moment of face-to-face interaction. Bourelle's (2014) empirical study showed that "working and communicating as an actual member of an organization" gives students a valuable glimpse into workplace culture (p. 173). However, she has noted an occasion where the industry mentor was not able to provide the support the student needed.…”
Section: Industry Mentorsmentioning
confidence: 99%
“…In contrast to "hard" skills that rely on technical content knowledge, "soft skills" are often viewed as "non-cognitive" [52] and affective qualities or abilities that are not taught in school. Like entrepreneurship, soft skills have enjoyed significant attention in TPC scholarship, often in connection to internships [6,40] or fostering communication skills [1,8,9]. One reason for this attention is that soft skills have been identified as important for success across professional workplaces [20,32].…”
Section: Soft Skillsmentioning
confidence: 99%
“…In technical and professional communication (TPC), community-engaged learning 1 has become an important component of university curricula for many reasons. Community-engaged learning provides students with authentic environments (Bourelle, 2014b;Bowdon & Scott, 2002) and a variety of rhetorical situations (Bourelle, 2014b;Youngblood & Mackiewicz, 2013). It shows students the real-life impacts of their writing, teaches them how to navigate complex problems and engage in course materials more deeply, and encourages them to take more responsibility for their own success (Kimme Hea & Wendler Shah, 2016;Soria & Weiner, 2013).…”
Section: Introductionmentioning
confidence: 99%